Radionuclide carriers for targeting of cancer - Stavroula Sofou (Dove Medical Press, 2008)
Stavroula SofouLaboratory for Drug Delivery Systems, Othmer-Jacobs Department of Chemical and Biological Engineering, Polytechnic University, Brooklyn, NY, USAAbstract: This review describes strategies for the delivery of therapeutic radionuclides to tumor sites. Therapeutic approaches are summarized in terms of tumor location in the body, and tumor morphology. These determine the radionuclides of choice for suggested targeting ligands, and the type of delivery carriers. This review is not exhaustive in examples of radionuclide carriers for targeted cancer therapy. Our purpose is two-fold: to give an integrated picture of the general strategies and molecular constructs currently explored for the delivery of therapeutic radionuclides, and to identify challenges that need to be addressed. Internal radiotherapies for targeting of cancer are at a very exciting and creative stage. It is expected that the current emphasis on multidisciplinary approaches for exploring such therapeutic directions should enable internal radiotherapy to reach its full potential.Keywords: cancer radiotherapy, targeted radiotherapy, radiotherapy of micrometastases, radiotherapy of solid tumors, radiotherapy of tumor vasculature